1909
DOI: 10.1002/cber.19090420428
|View full text |Cite
|
Sign up to set email alerts
|

Die Existenz echter Percarbonate und ihre Unterscheidung von Carbonaten mit Krystall‐Wasserstoffsuperoxyd

Abstract: 1 liest: kurze %us:~inn~eiistttll~~ii~ nieir,er eraten 13eoLaclttungen zeiKt, rlall, e j sicli ltier uni eiue gnnze k'iillr ron l.:inzeleracheiiiungen lian-&It, cleren %risanirnerihang erht tlurcli eine griinclliclie Analyse tlrr ~eraiichshedillgungeii nufgekliirt \verrlen kann. I3rsonders niuU fest-,gestellt. \ver(lru, wie weit sic11 (lie i\naliJgie i n i t , dem L e n a r c l -1\01 Isclien I'liiiuonien erstreckt liinsichtlicli tler J3etleutring einer elektriscltcn I ,:it 111 II g d e s z 11 zerst ii 11 be n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1910
1910
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 6 publications
0
7
0
1
Order By: Relevance
“…In fact, we should briefly remember that carbonate enters the reaction mechanism of H 2 O 2 generation through the formation of peroxydicarbonate (eqs –) by electrogenerated hydroxyl radicals (eq ). ,,− 2 BDD ( OH ) + 2 CO 3 2 2 BDD + C 2 O 6 2 + 2 OH C 2 O 6 2 + 2 H 2 normalO 2 HCO 3 + H 2 O 2 …”
Section: Resultsmentioning
confidence: 99%
“…In fact, we should briefly remember that carbonate enters the reaction mechanism of H 2 O 2 generation through the formation of peroxydicarbonate (eqs –) by electrogenerated hydroxyl radicals (eq ). ,,− 2 BDD ( OH ) + 2 CO 3 2 2 BDD + C 2 O 6 2 + 2 OH C 2 O 6 2 + 2 H 2 normalO 2 HCO 3 + H 2 O 2 …”
Section: Resultsmentioning
confidence: 99%
“…The reaction mixture was stirred manually with the anodecarrying thermometer throughout the synthesis, which normally lasted 2 h. The reaction vessel was surrounded by a rock salt/ice mixture at -20°C, and the temperature of the electrolytic solution was not allowed to rise above -6°C. Later we used a modification of Riesenfeld and Reinhold's (1910) procedure, using a U-shaped reaction vessel surrounded by an alcohol/dry ice-cooling bath at -30°C to -40°C. The anode and the cathode compartments were separated by a medium porosity sintered glass plate, which increased the resistance to ion flow, and therefore to electric current.…”
Section: Methodsmentioning
confidence: 99%
“…Of these the following need to be mentioned, Tanatar (1899), who described a synthetic route that avoided the electrolytic procedure; Wolffenstein and Peltner (1908), who pointed out that simple carbonates can form complex salts with H 2 O 2 of crystallization, and described the synthesis of peroxycarbonates by the addition of CO 2 to alkali peroxides; Riesenfeld and Reinhold (1910) who improved on Constam and Von Hansen's electrolytic method; and Riesenfeld and Mau (1911) who studied the products obtained from alkali peroxides and hydroperoxides and demonstrated that they differ only with respect to the crystallization ligand which can be either H 2 O or H 2 O 2 . Partington and Fathallah (1950) summarized and reviewed the early literature on the subject of percarbonates.…”
Section: Introductionmentioning
confidence: 99%
“…The product was isolated by precipitation with ethanol. It was not correctly identified as a hydrogen peroxide addition compound until 1909, when RIESENFELD and REINOLD elucidated its structure [198]. Three major processes are used for the industrial manufacture of sodium percarbonate, yielding products with different properties with regard to bulk density, active oxygen content, and stability.…”
Section: Productionmentioning
confidence: 99%